The Effect of Simple Experiments on the Science Process Skills of 5-6 Year Old Children - Santi M. J. Wahid; Anwar Marasabesy; Jumiati Mododahi; Hasma N. Majia (Journal of Childhood Development, 2024)
This study aims to: (1) determine the application of simple experimental activities in children aged 5-6 years at Al-Khairat Kalumpang Kindergarten, (2) know the science process skills of children aged 5-6 years at Al-Khairat Kalumpang Kindergarten, (3) know the effect of simple experiments on the science process skills of children aged 5-6 years at Al-Khairat Kalumpang Kindergarten. This type of research is Quantitative Research with a research design using One Group Pretest-Postest Design. The population and sample of the study were 20 children of group B1. Data Collection Techniques through observation and documentation and data are analyzed through Normality test and t-Test. The results of this study show that (1) the application of simple experimental activities is carried out through three treatments, namely the Floating Drowning experiment, the experiment of dissolving and insoluble in water and the experiment of objects that absorb and do not absorb water, (2) Science Process Skills for children aged 5-6 years in Al-Khairat Kalumpang Kindergarten, namely Observation Skills, Grouping / Classifying Skills and Communication Skills. This can be seen in the value of each stage carried out, namely during the pre-test (5.95%), the first treatment (Experiment I) of (6.65%), the second treatment (Experiment II) of (8.75%), the third treatment (Experiment III) of (10.9%) and the post-test of (13.5%). (3) Simple Experiment has an effect on children's science process skills based on the results of the t-count test is -19.615 with a significant level of 0.001. Because of the significant <0.05, it can be concluded that Ho was rejected and H1 was accepted which means that there is a simple experimental effect on the science process skills of children aged 5-6 years in Al-Khairat Kalumpang Kindergarten.